Raptors of the Pacific Northwest - Bosakowski, Thomas; Smith, Dwight G. (Frank Amato Publications, 2002)
Keywords: Birds of prey; Identification; Northwest, Pacific; Northwest, Pacific; Birds of prey; dept.egm; faculty_collection

Great Horned Owl - Smith, Dwight G. (Wild bird guides, 2002)
Keywords: Great horned owl; dept.egm; faculty_collection

Citrate-mediated increase in the uptake of weathered 2,2-bis(p-chlorophenyl)1,1-dichloroethylene residues by plants - White, Jason C; Kottler, Bennett D (Environmental Toxicology and Chemistry, 2002)
Experiments were conducted to determine the ability of citrate to enhance the plant uptake of weathered 2,2-bis(p-chlorophenyl)1,1-dichloroethylene (p, p′-DDE) from soil. Plots containing three rows of clover, mustard, hairy vetch, or rye grass were constructed in soils containing p, p′-DDE. On 11 occasions, the rows of each crop received water or sodium citrate (0.005 or 0.05 M). For each crop, there were significant reductions in p, p′-DDE concentration in the soil fractions (near root and rhizosphere) closely associated with the plant versus bulk soil. The roots of each crop accumulated 2 to 5 times more of the weathered contaminant (dry wt) than present in the bulk soil. Citrate (0.05 M) increased the concentration of p, p′-DDE in the roots of clover, mustard, and hairy vetch by 39% compared with vegetation that received water. In batch desorption studies, the release of weathered p, p′-DDE was significantly greater in the presence of 0.05 M citrate than in water. Citrate increased the extracted aqueous concentrations of five metal ions (Al, Fe, Ca, K, Mn) from soil by five- to 23-fold over distilled water. We hypothesize that citrate physically disrupts the soil through chelation of structural metal ions and release of bound humic material, facilitating p, p′-DDE availability and uptake by plants.
Keywords: 1,1 dichloro 2,2 bis(4 chlorophenyl)ethylene; Bioavailability; Biodegradation, Environmental; Brassica; Chelating Agents; Chelation; Citric Acid; Dichlorodiphenyl Dichloroethylene; Drug Interactions; Extraction; Humic Substances; Impurities; Insecticides; Ions; Metals; Organic compounds; Phytoremediation; Plants; Plants (botany); Secale cereale; Sequestration; Soil Pollutants; Soil fractions; Soil pollution; Tissue Distribution; Trifolium; Vegetation; Vicia; Vicia villosa; Water; aluminum; aqueous solution; article; bioavailability; biological uptake; bioremediation; calcium; chelation; citric acid; clover; concentration (parameters); dept.egm; desorption; iron; manganese; metal ion; nonhuman; phytoremediation; plant; plant root; potassium; priority journal; rhizosphere; rye; soil pollution; water